Banking 4.0 -The impact of Industry 4.0 on current Business Banking Business models in a big South African Bank - Böhmer, Helena M (My University, 2020)
Industry 4.0 is inevitable. Banks need to ensure that business models enable them to adapt the way they do business and be ready scale their product offerings in line with the rapid changing technology. Financial technology (known as Fintech) is also a reality. Fintech seeks to improve and automate the delivery and use of financial services. This also introduces competition of new entrants to the market. With the dawn of Fintech, banking will have to adopt and ensure they are on par with this technology. But how will banks adapt to this change and are they ready to change? For this study a theoretical framework was used to measure the readiness of a big South African bank. This framework includes, gamification, blockchain technology, biometric technology, digital investment and process optimization. A qualitative approach, using semi-structured interviews with subject matter experts, was done. This was followed by thematic content analysis using coding as the research method. New pillars emerged from the research. These are human resources, big data and security and were identified as important items for this transformation. These were some of the main findings that were included in the updated framework
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020